2020
DOI: 10.1002/tax.12204
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic lineages and the role of hybridization as driving force of evolution in grass supertribe Poodae

Abstract: To investigate the evolutionary diversification and morphological evolution of grass supertribe Poodae (subfam. Pooideae, Poaceae) we conducted a comprehensive molecular phylogenetic analysis including representatives from most of its accepted genera. We focused on generating a DNA sequence dataset of plastid matK gene-3′trnK exon and trnL-trnF regions and nuclear ribosomal (nr) ITS1-5.8S gene-ITS2 and ETS that was taxonomically overlapping as completely as possible (altogether 257 species). The idea was to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(110 citation statements)
references
References 113 publications
8
97
0
5
Order By: Relevance
“…Complete and partial plastomes as well as the nuclear rDNA cistron and ITS data supported the phylogenetic placement of the studied Fernandezian Podophorous bromoides, Megalachne berteroniana, and M. masafuerana species within the American-Vulpia-Pampas fine-leaved Loliinae clade (Figures 2, 3 and Supplementary Figures S1A-C). Our results corroborate the early suggestions of Tateoka (1962) who indicated a close affinity of Megalachne to Festuca based on shared morphological and serological traits, and the recent phylogenetic findings of Schneider et al (2011Schneider et al ( , 2012 and Tkach et al (2020) who placed them within the fine-leaved Loliinae, and definitively discard its classification within either Bromeae or Duthieinae. Our results have also contributed to enlarge the paraphyly of Festuca, which now accounts to up to 14 Loliinae genera nested within its main fine-leaved (Ctenopsis, Dielsiochloa, Hellerochloa, Megalachne, Micropyrum, Narduroides, Podophorus, Psilurus, Vulpia, Wangeheimia), intermediate (Castellia), and broad-leaved (Lolium, Micropyropsis, Pseudobromus) lineages (Supplementary Figure S2C; Inda et al, 2008;Minaya et al, 2017).…”
Section: Phylogenetics Of Megalachne and Podophorus: The Loliinae Fersupporting
confidence: 90%
See 3 more Smart Citations
“…Complete and partial plastomes as well as the nuclear rDNA cistron and ITS data supported the phylogenetic placement of the studied Fernandezian Podophorous bromoides, Megalachne berteroniana, and M. masafuerana species within the American-Vulpia-Pampas fine-leaved Loliinae clade (Figures 2, 3 and Supplementary Figures S1A-C). Our results corroborate the early suggestions of Tateoka (1962) who indicated a close affinity of Megalachne to Festuca based on shared morphological and serological traits, and the recent phylogenetic findings of Schneider et al (2011Schneider et al ( , 2012 and Tkach et al (2020) who placed them within the fine-leaved Loliinae, and definitively discard its classification within either Bromeae or Duthieinae. Our results have also contributed to enlarge the paraphyly of Festuca, which now accounts to up to 14 Loliinae genera nested within its main fine-leaved (Ctenopsis, Dielsiochloa, Hellerochloa, Megalachne, Micropyrum, Narduroides, Podophorus, Psilurus, Vulpia, Wangeheimia), intermediate (Castellia), and broad-leaved (Lolium, Micropyropsis, Pseudobromus) lineages (Supplementary Figure S2C; Inda et al, 2008;Minaya et al, 2017).…”
Section: Phylogenetics Of Megalachne and Podophorus: The Loliinae Fersupporting
confidence: 90%
“…Nonetheless, the comprehensive morphological and molecular study of the newly delimited tribe Duthieeae of Schneider et al (2011) demonstrated, using ITS sequences, that Megalachne and Podophorus were not part of this early diverging pooid lineage, and suggested that they likely belonged to the Aveneae/Poeae complex. In recent studies, phylogenetic analyses conducted by Schneider et al (2012) and Tkach et al (2020) using, respectively, nuclear ITS and plastid matK sequences and nuclear ITS and ETS and plastid matK, trnK, and trnLF sequences corroborated it, showing that Megalachne was nested within the fine-leaved Loliinae clade.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…During herbarium research at the United States National Herbarium (US), specimens of Agrostis meyenii Trin., a species recorded further south in Bolivia, Argentina, and Chile (Renvoize 1998;Rúgolo de Agrasar 2012;Jørgensen et al 2014), were encountered and mark the northernmost distribution of this species recorded to date. With the addition of A. meyenii, and including taxa previously circumscribed in Bromidium based on indications from recent phylogenetic research (Tkach et al 2020), it is currently estimated that 13 species of Agrostis are present in Peru (A. breviculmis Hitchc. ; A. foliata Hook.f.…”
Section: Introductionmentioning
confidence: 99%